Makna Simbolik Arsitektur Pada Rumah Kampung Kemasan Di Kelurahan Pekelingan Kecamatan Gresik Kabupaten Gresik - Qurrotul Uyun; I Wayan Arsana (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
The research is motivated by the meaning of the symbols contained in the architecture of packaged village houses in Pekelingan Village, Gresik District, Gresik Regency. The aims of this study is; 1) To find out the architectural symbols contained in the Kampung Kemasan House; 2) Indetify the meaning of the symbols in the architecure of the Kampung Kemasan House in Pekelingan Village, Gresik District, Gresik Regency. This research uses qualitative methods using a descriptive approach and for data collection techniques using interview, observation, and documentation methods. The results of this study show that the Kampung Kemasan house building is a building whose architecture is influenced by Europeans, Chinese, and Arabs. The meaning of symbols contained in the architecture of the Kampung Kemasan house building in Pekelingan Village, Gresik District, Gresik Regency includes doria pillars (sturdy, magnificent and monumental), tendrils (hope containing prayers), piles of bricks (ornamental variety), octagon / squares floors (prosperity, victory), flora/climb symbols (strong and confident establishments), double doors (ornamental varieties), spear fences (strength), spear fence (strength), fatma flower (beauty,loyalty), Red color (prosperity, luck, benevolence and courage).